2020
DOI: 10.26452/ijrps.v11ispl2.2098
|View full text |Cite
|
Sign up to set email alerts
|

A study comparing two different pinning techniques in supracondylar fractures of the humerus

Abstract: Various treatment options are available for treating type III supracondylar fractures of the humerus. The most common technique employed is closed manipulative reduction with K wire fixation. This study was performed to compare two different pinning techniques in type III supracondylar fractures of the humerus. This study was done in the time frame between January 2012 to December 2015. The age of the children selected for this study ranged from 3 to 12 years of age. Among 66 children, 6 were lost to follow up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their systematic review, Brauer et al 10 found that iatrogenic nerve injury occurred in 3.5% of patients who had cross pinning and in 1.9% of patients with lateral pinning. In spite of the higher incidence of nerve injury with cross pinning, 14 its superior biomechanical stability is well established. 10,15 Lateral pinning was suggested by the American Academy of Orthopaedic Surgeons (AAOS) to avoid ulnar nerve injury with a weak level of evidence.…”
mentioning
confidence: 99%
“…In their systematic review, Brauer et al 10 found that iatrogenic nerve injury occurred in 3.5% of patients who had cross pinning and in 1.9% of patients with lateral pinning. In spite of the higher incidence of nerve injury with cross pinning, 14 its superior biomechanical stability is well established. 10,15 Lateral pinning was suggested by the American Academy of Orthopaedic Surgeons (AAOS) to avoid ulnar nerve injury with a weak level of evidence.…”
mentioning
confidence: 99%